Long-term spatiotemporal stability and dynamic changes in helminth infracommunities of spiny mice (Acomys dimidiatus) in St. Katherine's Protectorate, Sinai, Egypt. Issue 1 (20th June 2018) - Behnke, Jerzy M.; Bajer, Anna; Behnke-Borowczyk, Jolanta; Clisham, Natalie; Gilbert, Francis; Glover, Aimee; Jeffery, Laura; Kirk, Jonathan; Mierzejewska, Ewa J.; Mills, Simon C.; Mohallal, Eman M. E.; Padget, Oliver; et al.
Abstract: The importance of parasites as a selective force in host evolution is a topic of current interest. However, short-term ecological studies of host–parasite systems, on which such studies are usually based, provide only snap-shots of what may be dynamic systems. We report here on four surveys, carried out over a period of 12 years, of helminths of spiny mice ( Acomys dimidiatus ), the numerically dominant rodents inhabiting dry montane wadis in the Sinai Peninsula. With host age (age-dependent effects on prevalence and abundance were prominent) and sex (female bias in abundance in helminth diversity and in several taxa including Cestoda) taken into consideration, we focus on the relative importance of temporal and spatial effects on helminth infracommunities. We show that site of capture is the major determinant of prevalence and abundance of species (and higher taxa) contributing to helminth community structure, the only exceptions being Streptopharaus spp. and Dentostomella kuntzi. We provide evidence that most (notably the Spiruroidea, Protospirura muricola, Mastophorus muris and Gongylonema aegypti, but with exceptions among the Oxyuroidae, e.g. Syphacia minuta ), show elements of temporal-site stability, with a rank order of measures among sites remaining similar over successive surveys. Hence, there are some elements of predictability in these systems.